Preservice Subject Teachers’ Lack of Interest in Their Minor Subject: Is It a Problem? - Havia, Johanna; Lutovac, Sonja; Komulainen, Tiina; Kaasila, Raimo (International journal of science and mathematics education, 2023)
Interest in a particular subject is one central factor in preservice teachers’ decision to become subject teachers. Interest in a subject can also become visible in preservice teachers’ teaching and may consequently impact their students’ interest in the subject. However, the interest of preservice teachers in their major and minor subjects has been scarcely addressed. In Finland, secondary school teachers usually study and teach two or three subjects. Major subjects are often chosen based on interest; however, the reasons for choosing a minor subject can vary. In this study, we examined the narratives of three preservice subject teachers regarding their interest in their minor and major subjects. They all studied mathematics, physics, and chemistry and revealed a much weaker interest in the minor subjects compared to the major subjects. Interestingly, our findings also reveal that preservice teachers’ perceived strengths in a specific subject may not be as crucial to their interests, as has been suggested by prior research. We discuss the consequences of preservice teachers’ weaker interest in certain subjects and provide recommendations for teacher education.